Oral anticoagulants increased 30-day survival in sepsis patients complicated with atrial fibrillation: a retrospective analysis from MIMIC-IV database - Ge, Gaoyuan; Bo, Dan; Jiang, Rongli; Zhao, Wei; Lu, Yao (Frontiers in Cardiovascular Medicine, 2024)
Background:The severity of sepsis is associated with systemic clotting activation.Atrial fibrillation (AF) is the most commonly observed arrhythmia in patients with sepsis and can lead to a poor prognosis. The aim of this study is to elucidate the association between oral anticoagulants and survival from septic patients complicated with AF.: The data of 8,828 septic patients, including 2,955 AF and 5,873 without AF, were all originated from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Patients with sepsis and AF are divided into OAC-group (n=1774) and OAC+ group (n=1,181) based on OAC therapy. Septic patients with no AF were considered as the control group (n= 5873, sepsis and no AF group). The main outcome endpoint was the survival rate of 30 day. The secondary outcome endpoint was the length of stay (LOS) from intensive care unit and hospital. Propensity score matching (PSM) was used to adjust the influence of superfluous factors, and a restricted mean survival time (RMST) analysis was used for calculating the benefit of survival time and survival rate.Analysis including univariate and multivariate logistic regression analysis was conducted to find prognosis-related predictors.Results: After PSM, the OAC+ group had a higher 30-day survival rate compared to the OAC-group (81.59%vs.58.10%; P < 0.001) in the ICU. Despite the higher survival, the hospital LOS (14.65 days vs. 16.66 days; P = 0.15) and ICU LOS (6.93 days vs. 5.92 days; P = 0.02) were prolonged at OAC+ group than OAC-group. No difference was found in survival rate of 30 day between the sepsis patients using warfarin and patients using NOAC (85.60% vs.79.84%, P = 0.12). The sepsis patients using warfarin had a prolonged LOS in ICU and hospital compared with the sepsis patients using NOAC. In the vasopressor subgroup, patients who received NOAC therapy were associated with a reduced 30-day survival rate (73.57% vs.84.03%; P = 0.04) and reduced LOS in ICU and hospital than those on warfarin therapy.This study demonstrated that oral anticoagulants may increase the 30-day survival rate of patients with sepsis and AF.